Pengaruh Penggunaan Media Video Animasi Pada Pembelajaran Tematik Terhadap Hasil Belajar Siswa Kelas V SD - Sari, Mirda Dwi Puspa; Anggraini, Dwi; Noperman, Feri (Universitas Bengkulu, 2025)
The purpose of this research is to examine the effects of animated video material on the academic performance of fifth-grade students at SDN Bengkulu City. This quantitative study used the Quasi Experiment method and a matched-pairs pretest-posttest control-group layout. Students in the fifth grade at SDN Cluster XII in Bengkulu City are the subjects of this study. This research included 28 students from Class V SDN 99 in the City of Bengkulu and 32 students from Class V SDN 81 in the same city. Cluster random sampling is the method that will be used. A sheet with multiple-choice questions served as the test's medium. Pre- and post-lesson exams were administered to students in both the experimental and control groups. Descriptive analysis, precondition tests, and inferential testing were all used in this study's examination of the collected data. Based on the data and analysis, it was determined that the t-test for scientific themes has a t-count value of 4.116 and a t-table value of 2.002, whereas the same test for Indonesian subjects has a t-count value of 4.463 and a t-table value of 2.002. Using a tcount > table at the 5% level of significance, we find that class V SDN Bengkulu City students' learning outcomes improve when animated video media is used for thematic learning.